Experimental Vertical Transmission of Chikungunya Virus by Brazilian and Florida Aedes Albopictus Populations - Honório, Nildimar Alves (Viruses, 2019)
Chikungunya virus (CHIKV) is a vector-borne alphavirus transmitted by the bites of mosquitoes, specifically infected, female mosquitoes of the invasive Aedes species. In nature, CHIKV can be maintained by vertical transmission, a phenomenon that relates to the transfer of CHIKV from the infected parent to their offspring within the ovary or during oviposition. In the present study, we conducted laboratory experiments to determine vertical transmission with Ae. albopictus populations from Brazil and Florida. Parental Ae. albopictus females were orally infected with the emergent Asian genotype of CHIKV in the first gonotrophic cycle (infectious blood meal) and tested for vertical transmission following the second (non-infectious blood meal) gonotrophic cycle. CHIKV infection and CHIKV viral titer in parental females were significantly related to population origin, with Brazilian Ae. albopictus showing higher viral dissemination and viral titer than the Florida population. Experimental vertical transmission of CHIKV was documented in one pool of female and four pools of male Ae. albopictus from Brazil (minimum infection rate, MIR, of 0.76% and 2.86%, respectively, for females and males). For the Florida population of Ae. albopictus, only one pool of males was positive for CHIKV infection, with an MIR of 1.06%. Our results demonstrate that Ae. albopictus populations from Brazil and Florida show heterogeneous CHIKV dissemination and vertical transmission, which may contribute to the epidemiology of CHIKV and may be particularly relevant to virus survival during inter-epidemic periods.